DIPLOMASI INDONESIA UNTUK MENDORONG AMERIKA SERIKAT MENCABUT KEBIJAKAN LARANGAN IMPOR ROKOK KRETEK - , Muhammad Hadidarma Ramadhani, Dr. Nanang Pamuji Mugasejati ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The exporting of Indonesian clove cigarettes to various countries has become one of Indonesiaâs biggest deposit incomes and has opened widespread job opportunities for Indonesian people. The USA is one country which Indonesia has exported clove cigarettes to for thirty years and each year has brought considerable deposit income for Indonesia. Since 2009, however, Indonesia no longer receives this deposit income due to a policy issued by the USA banning the import of clove cigarettes through the newly introduced Family Smoking Prevention and Tobacco Control Act. This policy is a threat to Indonesia clove cigarette industries and to Indonesiaâs continuation of exporting clove cigarettes to other countries. The USAâs policy has become a recent trendsetter for other countries to introduce a similar policy. If that happens, it is possible that other countries will also ban Indonesian clove cigarettes, potentially causing a large loss in Indonesiaâs deposit income. According to Indonesia, this policy is against the World Trade Organizationâs anti-discrimination principle. Clove cigarettes are a similar product to menthol cigarettes, and while clove cigarettes are a banned product in the USA, menthol cigarettes remain legal there. The Indonesian government and non-government organizations have tried to pursue the US government through diplomacy in attempts to revise the policy. But such attempts by Indonesian actors have so far proven unsuccessful. The difficult pursuit of the USA government to revise and/or alter the policy has depended on the Indonesian actorsâ role and the implementation of Indonesiaâs international trade policies. The purpose of this research is to understand the difficulties of Indonesian actors in pursuing the USA actors to revise and/or alter the policy through a diplomatic approach. The methods that will be used by the researcher include an interview with an actor from Indonesiaâs Ministry of Trade, analyzing government and nongovernment documents, mapping actors who were involved with this case, and analyzing the trade policy.